Central sleep apnea detection from ECG-derived respiratory Signals: application of multivariate recurrence plot analysis - Maier, Christoph; Dickhaus, Hartmut (Methods of information in medicine, 2010)
This study examines the suitability of recurrence plot analysis for the problem of central sleep apnea (CSA) detection and delineation from ECG-derived respiratory (EDR) signals.